Pengetahuan Dan Sikap Pasien Dalam Mencegah Kekambuhan Dari Serangan Jantung Di Ruang Poli Jantung - Wahyu Dini Metrikayanto; Ani Sutriningsih; Yumiati Leda Bouka (Nursing News : Jurnal Ilmiah Keperawatan, 2022)
Heart attack is one of the causes of sudden death. To prevent recurrence of heart attacks, good knowledge and attitudes towards a healthy lifestyle are needed. The aim of the study was to find out the knowledge and attitudes of patients in preventing recurrence of heart attacks in the Cardiac Poly Room, Panti Waluyo Sawahan Hospital, Malang City. This research method uses descriptive quantitative on 30 respondents using systematic random sampling technique and using a questionnaire instrument. The population of this study were all heart attack patients in the Heart Polyclinic Room of Panti Waluyo Sawahan Hospital, Malang City with a total sample of 30 people. Samples were taken by systematic random sampling technique. The variables studied were knowledge and attitudes about heart attack prevention. The measuring tool to determine both knowledge and attitude variables is a questionnaire. The results form this study showed that the majority of patients had less knowledge (56.7%) and attitude in preventing recurrence of heart attacks in the poor category (70.0%). Suggestions that can be given from this study are provide education about preventing recurrence of heart attacks through media images and videos that patients and families can read and watch when controlling or visiting the hospital.